2009
DOI: 10.1177/1479164109350556
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetic patients with resistant hypertension should be screened for primary aldosteronism

Abstract: BP control in diabetic patients is often poor. The contribution of secondary hypertension due to undiagnosed PA in hypertensive type 2 diabetic patients is not well studied. We prospectively screened 100 consecutive Asian type 2 diabetic patients with difficult-to-control or resistant hypertension for PA. PAC (pmol/L) to PRA (ng/mL/h) ratio was measured; those with PAC-to-PRA ratio >550 (corresponding PAC >415) underwent intravenous 0.9% SLT. Patients with PAC >/=140 following SLT had CT adrenals and bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 46 publications
1
30
2
Order By: Relevance
“…The prevalence of PA in this study was significantly lower than that demonstrated in other worldwide studies reported in the past twenty years (7,(14)(15)(16)(17)(18)(19)(20). This may be attributable to several factors.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The prevalence of PA in this study was significantly lower than that demonstrated in other worldwide studies reported in the past twenty years (7,(14)(15)(16)(17)(18)(19)(20). This may be attributable to several factors.…”
Section: Discussioncontrasting
confidence: 55%
“…Since the validation of the aldosterone: renin ratio (ARR) as a reliable method for identifying PA, several global studies have reported PA prevalence rates ranging from 3-22% (7-14) with even higher rates reported (13-33%) in certain sub-populations, such as those with resistant hypertension and hypertension associated with diabetes or obstructive sleep apnea (15)(16)(17)(18)(19)(20). These findings may justify broader criteria for screening for PA.…”
Section: Introductionmentioning
confidence: 98%
“…However, another study was not able to con fi rm the association between metabolic syndrome and PA [ 68 ] . Finally, a recent retrospective study from the German Conn's Registry, showed that PA patients displayed a higher rate of diabetes compared to a control population of essential hypertensives [ 69 ] and others reported a high prevalence of PA in type 2 diabetic patients with resistant hypertension [ 70,71 ] .…”
Section: Clinical Features and Complications Of Pamentioning
confidence: 97%
“…PA caused by aldosteroneproducing adenoma or unilateral adrenal hyperplasia shows an increasing trend, with a reported prevalence of around 20% in resistant hypertensive patients [12], and the incidenceis higher in patients with Type 2 DM [13]. Maintained hypervolemia plays a key role in remaining resistant.…”
Section: ) Primary Aldosteronism (Pa)mentioning
confidence: 99%